Environmental education and community empowerment for local fish conservation in Pasuruan, Indonesia - Hamdani Dwi Prasetyo; Husain Latuconsina; Nour Athiroh Abdoes Sjakoer; Gatra Ervi Jayanti (University of Merdeka Malang, 2026)
Pusat Konservasi Iwak Kali (PAKWALI) in Bakalan village, Pasuruan, holds significant potential for freshwater biodiversity conservation, but faces major challenges from environmental pollution, exploitation of native fish species, and limited infrastructure support. This community services program aimed to strengthen conservation efforts through community empowerment, education, and facility support. The main objectives were to raise awareness of local fish conservation, improve water quality management, and build capacity through participatory training. The program was implemented through several stages, including site assessment, installation of basic facilities such as fish nursery ponds and water quality monitoring tools, community education workshops, and post-activity evaluation. Pre- and post-test analysis showed improvements in cognitive, affective, and psychomotor dimensions. Affective scores increased from 4.25 to 4.62 (p = 0.023), indicating a statistically significant improvement in participants’ conservation attitudes. Results showed increased community understanding of freshwater ecosystems, greater awareness of the importance of native fish species, and growing motivation among participants to adopt sustainable fish farming practices. Additionally, the use of standardized recording formats and expanded partnerships with academic and environmental institutions supported the long-term sustainability of the program. The initiative demonstrates the effectiveness of local based conservation efforts in integrating ecological education with practical community-based action.